2018
DOI: 10.1021/acs.orglett.8b02172
|View full text |Cite
|
Sign up to set email alerts
|

[3 + 2] Cycloaddition of Nitrile Ylides with Diazonium Salts: Copper-Catalyzed One-Pot Synthesis of Fully Substituted 1,2,4-Triazoles

Abstract: A novel [3 + 2] cycloaddition between nitrile ylides and diazonium salts was well-established. This copper-catalyzed three-component reaction was distinguished by mild conditions, ready availability, and operational simplicity, thus opening access to 1,2,4-triazoles with a diverse set of substitution patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 62 publications
(15 reference statements)
0
18
0
1
Order By: Relevance
“…Among them, we reported a copper‐catalysed three‐component transformation to CF 3 ‐oxazolines in 2015 by harnessing the reactivity of nitrile ylides in situ generated from trifluorodiazoethane and nitriles . Subsequently, Wan and Bao developed a [3+2] annulation reaction of ester‐derived nitrile ylides with aryldiazonium salts to form N 1 ‐aryl‐5‐carboxylic‐1,2,4‐triazoles . Inspired by these studies and as part of our continuing interest in fluoroalkyl heterocycles, here we present the synthesis of both difluoro‐ and trifluoromethylated N 1 ‐aryl‐1,2,4‐triazoles enabled by a novel multicomponent reaction of aryldiazonium salts with fluorinated diazo reagents and nitriles (Scheme b) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, we reported a copper‐catalysed three‐component transformation to CF 3 ‐oxazolines in 2015 by harnessing the reactivity of nitrile ylides in situ generated from trifluorodiazoethane and nitriles . Subsequently, Wan and Bao developed a [3+2] annulation reaction of ester‐derived nitrile ylides with aryldiazonium salts to form N 1 ‐aryl‐5‐carboxylic‐1,2,4‐triazoles . Inspired by these studies and as part of our continuing interest in fluoroalkyl heterocycles, here we present the synthesis of both difluoro‐ and trifluoromethylated N 1 ‐aryl‐1,2,4‐triazoles enabled by a novel multicomponent reaction of aryldiazonium salts with fluorinated diazo reagents and nitriles (Scheme b) .…”
Section: Methodsmentioning
confidence: 99%
“…The observed difference in regioselectivity profile of trifluorodiazoethane compared with phenylsulfone difluorodiazoethane might be attributed to the increased steric effect in the case of trifluoromethyl-substituted nitrile ylide intermediate. [8] The operational simplicity and broad compatibility of this multicomponent reaction promoted us to further explore the preparation of divergent difluoromethyl and trifluoromethyl analogues of P2X3 receptor antagonists (Scheme 7). [18] By operating aryldiazonium salt 9 with respective fluorinated diazo reagent in acetonitrile under standard copper catalysis conditions, four fluoroalkyl N 1 -aryl-1,2,4-triazoles 10 a, 10 b, 12 a, and 12 b were all routinely obtained.…”
Section: Updatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple and efficient strategy for the synthesis of structurally diverse 1,2,4-triazoles via copper-catalyzed three-component reaction was disclosed by Wan and co-workers (Scheme 27). [39] In their reactions, the aryldiazonium salts undergo [3 + 2] cycloaddition with nitrile ylides generated in situ from nitriles and diazo compounds to deliver the desired 1,2,4-triazoles in a one-step fashion under mild reaction conditions. A wide range of functional groups were well tolerated in this transformation.…”
Section: Synthesis Of 124-triazoles and Their Derivativesmentioning
confidence: 99%
“…In 2018, Wan and co‐workers reported the catalytic construction of 1,2,4‐triazoles 110 via the three‐component reaction of alkyl 2‐diazoacetates 78 , aryl diazonium salts 30 , and nitrile solvents (Scheme 27). [ 155 ] Mechanistic study suggested that Cu catalyst could react with alkyl 2‐diazoacetate to form a Cu‐alkylidene species 107 , which further coupled with nitrile to generate a nitrile ylide intermediate 108 . Nitrile ylide 108 then underwent [3 + 2] cycloaddition with aryl diazonium ion 30 to give a five‐membered aza‐cycle 109 , which finally isomerized in the presence of base to produce a series of tri‐substituted 1‐aryl‐1,2,4‐triazole‐ 3‐carboxylate products 110 .…”
Section: Cyclization and Cycloaddition Reactions For The Constructionmentioning
confidence: 99%